Educational research: Contemporary issues and practical approaches - Wellington,J. Jerry Wellington (London: Continuum, 2000)
"Any body embarking on a research project in education is likely to ask certain key questions: what is educational research?; what approaches are there?; what research has been done before?; how should research be conducted?; and what is the value of research? In this practical and accessible guide, Jerry Wellington provides clear and constructive answers to these questions, complete with detailed advice on interviewing, case studies, surveys, documentary research, the Delphi method and the use of focus groups."--Jacket
includes bibliographic reference and index
Keywords: Research -- Contemporary issues